Gender, Whiteness, and power in rodeo : breaking away from the ties of sexism and racism - Patton, Tracey Owens (Lexington, Books, 2012)
The cowboy and cowgirl played in the imagination and made rodeo into a symbolic representation of the Western United States, but the rodeo has diverse history that largely remains unaccounted for. In Gender, Whiteness and Power in Rodeo Tracey Owens Patton and Sally M. Schedlock visually explore how race, gender, and other issues of identity complicate the mythic historical narrative of the West. Using iconic visual images, along with the voices of the marginalized, Patton and Schedlock enter into the sometimes acrimonious debate of cowgirls and ethnic minorities in rodeo.